The Role Of Pentahelix Elements In The Tourism Development Process In Jati Tourism Village, Garut Regency - Kartika, Nurhasanah; Firmansyah, Deden; Dhamayanty, Stanny (Riwayat: Educational Journal of History and Humanities, 2024)
In the current era, there has been a shift in tourism trends from mass models to more sustainable activities involving loval community participation. Jati Tourism Village, which has been designated as a leading village in Garut Regency, was established as a Tourism Village based on Decree number 556/KBP.963-DPMD from the Head of the Tourism and Culture Office of Garut Regency, which designated this village as a Pioneering Tourism Village in Garut Regency. Over time, The tourist attraction requires development programs. This research explores the potential development of the tourism village through four main indicators: tourism village infrastructure development, tourism village marketing, institutionak strengthening, and actor partnerships. Using a qualitative descriptive approach, this study aims to analyze the rolw of stakeholders in the development of Jati Tourism Village, using the pentahelix framework, which consists of element from Academia, Business, Government, Community, and Media. The result show that stakeholders are able to play theie roles according to their respective responsibilities. Although some are considered less optimal. These obstacles pose challenges in achieving the goals og the Jati Tourism Village develpoment program. Field findings include a lack of understanding of regulations, limited funding, inadequate human resources, and insufficient coordination and collaboaration among stakeholders. Recommendations include addresing tourism needs, implementing intensive and sustainable training programs to improve the quality of human resouces, and creating formal Memorand of Understanding (MoU) that bind stakeholders together.